Detection of receptors for interleukin-6, interleukin-11, leukemia inhibitory factor, oncostatin M, and ciliary neurotrophic factor in bone marrow stromal/osteoblastic cells. - Bellido, T (1996)
The functional receptor complexes assembled in response to interleukin-6 and -11 (IL-6 and IL-11), leukemia inhibitory factor (LIF), oncostatin M (OSM), and ciliary neurotrophic factor (CNTF), all involve the signal transducer gp130: IL-6 and IL-11 induce homodimerization of gp130, while the rest heterodimerize gp130 with other gp130-related beta subunits. Some of these cytokines (IL-6, IL-11, and CNTF) also require a specificity-determining alpha subunit not directly involved in signaling. We have searched for functional receptor complexes for these cytokines in cells of the bone marrow stromal/osteoblastic lineage, using tyrosine phosphorylation of the beta subunits as a detection assay. Collectively, murine calvaria cells, bone marrow-derived murine cell lines (+/+LDA11 and MBA13.2), as well as murine (MC3T3-E1) and human (MG-63) osteoblast-like cell lines displayed all the previously recognized alpha and beta subunits of this family of receptors. However, individual cell types had different constellations of alpha and beta subunits. In addition and in difference to the other cell types examined, MC3T3-E1 cells expressed a heretofore unrecognized form of gp130; and MG-63 displayed an alternative form (type II) of the OSM receptor. These findings establish that stromal/osteoblastic cells are targets for the actions of all the members of the cytokine subfamily that shares the gp130 signal transducer; and suggest that different receptor repertoires may be expressed at different stages of differentiation of this lineage.